Verrucous systemic lupus erythematosus - Miteva, Ljubka (Array, 2009)
Summary:Few patients with systemic lupus erythematosus have features of verrucous (hypertrophic) lupus erythematosus. A 29-year-old Caucasian woman with a 7-year history of systemic lupus erythematosus developed painful verrucous plaques on the nose. Erythematous, raised, indurated, hyperkeratotic plaques localized on the dorsa of the distal parts of the toes and over the interphalangeal joints of her fingers were also noted. A large, dullred, indurated plaque with rolled borders on the bridge of the nose was most characteristic. Rapid therapeutic effect was obtained by systemic corticosteroid regimen. This verrucous variant of lupus erythematosus, sometimes clinically resembling actinic keratosis, keratoacanthoma and squamous cell carcinoma, is reviewed